ANALISIS TINGKAT KEPUASAN NASABAH TABUNGAN SIMPEDES ATAS KUALITAS PELAYANAN PT. BANK RAKYAT INDONESIA (PERSERO), TBK UNIT NGESREP SEMARANG - Ashiva, Dita Laila; Lubis, Nawazirul; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
PT. Bank Rakyat Indonesia is a company engaged in the field of financial services the largest and has the most extensive network in Indonesia. PT. Bank Rakyat Indonesia has also been successfully serving the financial needs of the Indonesian people’s for 119 years. PT. Bank Rakyat Indonesia (Persero), Tbk in providing services to their customers should be as optimal as possible so that they are satisfied. But in reality there is no indication of customer dissatisfaction over the quality of services provided by BRI Unit Ngesrep Semarang.The purpose of the research was to determine the extent to which the level of customer satisfaction BRI Unit Ngesrep Semarang on the quality of services provided to customers. The type of this research is descriptive analytical. The sample in this research were 98 respondents who are customers of savings simpedes at PT. BRI (Persero) Tbk Unit Ngesrep Semarang. The research data was collected using interview techniques, while the research instrument using a questionnaire. Data analysis using Importance and Performance Analysis. Based on the Importance and Performance Analysis, then be conclusion that the average total for the dimension of quality of service is 86,27 % include in the category are satisfied.Advice can be given for the company is to maximize the suggestion box, improving the condition of the parking BRI Unit Ngesrep Semarang, increase comfort lounge area and increase the speed of the queuing system.